2011
DOI: 10.1007/s11136-011-0060-z
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Dutch version of the VascuQol questionnaire and the Amsterdam linear disability score in patients with intermittent claudication

Abstract: The Dutch VascuQol is a valid and reliable questionnaire for assessment of Qol in patients with IC. This study confirms the good clinimetric properties of the ALDS for assessing disability in patients with IC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 14 publications
1
21
0
Order By: Relevance
“…The VascuQol has been validated in Dutch. 8,9 In the SUPER study the VascuQol and the generic Short Form (SF)-36 are sent to patients by mail at baseline, and after 1, 6, and 12 months. 5,10 A reminder is sent if a patient has not returned the questionnaires after a few weeks.…”
Section: Questionnairesmentioning
confidence: 99%
“…The VascuQol has been validated in Dutch. 8,9 In the SUPER study the VascuQol and the generic Short Form (SF)-36 are sent to patients by mail at baseline, and after 1, 6, and 12 months. 5,10 A reminder is sent if a patient has not returned the questionnaires after a few weeks.…”
Section: Questionnairesmentioning
confidence: 99%
“…The ICC in that study was 0.47 (95% CI 0.03e0.75), whereas this study found an ICC of 0.80 (95% CI 0.68e0.88). 5 The result is more precise due to a larger sample size.…”
Section: Discussionmentioning
confidence: 99%
“…4 Reliability for the English and Dutch VascuQol has been examined in just two studies, with 17 and 20 patients, respectively. 2,5 Although the VascuQol has been widely used in several languages for many years, its measurement error was never studied in any language. 3 The COnsensus based Standards for the selection of health Measurement INstruments (COSMIN) checklist, which was compiled in a Delphi study among international experts in the field of patient reported outcome measures (PROMS), indicates that at least 50 patients are necessary for good quality studies on reliability and measurement error.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies used included the Australian Vascular Quality of Life Index (AUSVIQOL) [37], the Vascular Quality of Life questionnaire (VASCUQOL) [10, 11], the Intermittent Claudication Questionnaire (ICQ) [14, 27], the Nottingham Health Profile (NHP) [40], the Health Utilities Index (HUI) questionnaire [2, 4] and Visual Analog Scales [9]. In total, 14 different QoL assessment tools were used across the 31 studies, with a total of 3928 patients surveyed.…”
Section: Number Of Questionnaires Usedmentioning
confidence: 99%
“…Of the 23 studies using SF-36 or a variant, 6 (26.09%) reported the results of 10 domains [11, 12, 14, 23, 34, 38], including a Physical Component Summary (PCS) and Mental Component Summary (MCS). The median reported domain in the SF-36 group was 8 (range 2–10).…”
Section: Number Of Incomplete Domainsmentioning
confidence: 99%